A new maximum color contrast sensitivity test for detecting early changes of visual function in age-related macular degeneration - Rasa Liutkevičienė; Džastina Čebatorienė; Dalia Žaliūnienė; Rita Lukauskienė; Vytautas Jašinskas (Medicina, 2014)
Background and objective: To determine the association between age-related macular degeneration (AMD) and color perception established by the Farnsworth–Munsell 100 hue (F–M 100) and maximum color contrast sensitivity (MCCS) tests. Materials and methods: We performed a case–control study, which comprised of 100 patients with AMD and 100 healthy controls. To test visual acuity (VA), a typical Snellen chart was used. The computerized F–M 100 and MCCS programs were used for color discrimination. Results: The results of VA, and the F–M 100 and MCCS tests in the healthy controls were statistically significantly better than in the patients with AMD (1.0 vs. 0.82 ± 0.16, P = 0.005; 87.39 ± 24.11 vs. 185.39 ± 74.43, P = 0.005; 1.33 ± 1.17 vs. 1.96 ± 0.46, P = 0.005, respectively). When VA was 1.0 in patients with AMD, the total error scores of the F–M 100 test and MCCS test compared with healthy persons were even worse (166.09 ± 66.57 vs. 87.39 ± 24.11, P = 0.002; 1.67 ± 0.92 vs. 1.33 ± 1.17, P = 0.001, respectively). Analysis of the results of patients with AMD compared to healthy controls showed the highest error score in the blue color range. Conclusions: The results of the color contrast sensitivity test decreased by half in patients with AMD compared with ophthalmologically healthy patients when they performed the F–M 100 test and by one and half when they performed a MCCS test in the blue color range.